Genetic theory and analysis finding meaning in a genome - Miller, Danny E.; Miller, Angela L.; Hawley, R. Scott (Wiley, 2023)
Since the first edition of this book was published, there have been many advances in genetics and genomics that are captured in this edition--to a point. Many genetics textbooks are geared either toward introductory undergraduate and/or medical students, providing primary information and touching on well-known historical milestones in biology. The spirit of this book has always been to consolidate and discuss key genetic studies from the literature then link those to current ideas in genetics. The goal is to provide a solid foundation to understand how genetic analysis was done in the past and link it to how it is being used today. For example, in the past, an investigator may have done a technically challenging screen to identify genes of interest in a biological pathway, while today, new sequencing technology could be used to identify mutations more easily in genes in that same pathway. Real-world clinical examples highlight the importance and relevance of the topics discussed to human disease. Finally, this edition will also include a glossary to make the content more accessible to undergraduates"--